ANALISISI PERFORMA BATERAI DALAM SISTEM PEMBANGKIT LISTRIK TENAGA SURYA PADA MESIN PENGUPAS KULIT SINGKONG - Zaid Sirajuddin; Ibrahim Lammada; Rahmat Hidayat (Power Elektronik : Jurnal Orang Elektro, 2023)
Cassava is a food that can be processed into various processed forms. Such as chips, tapai, tapioca flour and various other preparations. In the cassava processing process, thick cassava peeling is required, this raises the risk of work accidents. Therefore, many studies are looking for ways to make cassava skin peeling machines perfectly. In this research, an innovation was made to make a cassava skin peeling machine, by adding a slicing tool and using a source of electrical energy from a battery that can be recharged using a Solar Power Plant (PLTS), so that it can carry out the process of peeling cassava skin in a place far from energy sources. electricity, with the method used namely Research and Development (RD) as a process in conducting this research. So it is necessary to do a trial and analysis of the use of electrical energy with a load of a cassava peeler machine with a battery as a provider and store of electrical energy generated by the PLTS, this cassava peeler machine has a DC motor and a DC water pump as a load that requires electricity consumption. Therefore, measurements of current (I) and voltage (V) are carried out on the battery to obtain the value of the consumption of electrical energy that occurs in the battery.